MENINGKATKAN DURABILITAS CAMPURAN BETON ASPAL YANG MENGALAMI PROSES PENUAAN ASPAL SAAT KONSTRUKSI (SHORT TERM) DENGAN TEKNIK PENAMBAHAN KADAR ASPAL - Edward Ngii (STABILITA || Jurnal Ilmiah Teknik Sipil, 2013)
Abstract   Ageing is one of the small parts that causes damages and decreases to the flexible pavement construction strength especially the asphalt concrete mixture. Adding the asphalt content in the mixture is one of several ways to anticipate the ageing process in the asphalt mixture (Asphalt Institute, 2001).This research was performed by manufacturing the STOA samples (Brown dan Scholz,2000). Variation of adding asphalt content were 0.25%, 0.50% and 1.00% to the requirement from the optimum asphalt content (5.90%). The specification of asphaltic concrete mixture based on Kimpraswil 2002. The examination of strenght of the mixture was conducted by using the Marshall, Immersion and Cantabro test method.The results of this research indicated that base on the Marshall characteristics obtained the maximum value of the addition of aspahalt was at 0.50%. The condition was indicated decreasing strenght, but the stability value of 1371.82 kg, flow value of 3.50 mm and MQ value of 391.70 kg/mm were satisfied to the requirement. The Immersion Index value to the Immersion test of 48 hour by the addition of asphalt at 0.50% obtained 90.38%. The percentage loss of mass value after 300 times of rotation showed that the addition of asphalt at 0.50% obtained 4.64%. Keywords: Ageing bitumen, Asphaltic Concrete, Marshall tes.